PERBANDINGAN TEBAL PERKERASAN LENTUR METODE ANALISA KOMPONEN DAN AASHTO (STUDI KASUS: JALAN LUBUK ALAI - KOTO LAMO KABUPATEN LIMA PULUH KOTA) - Kurniawan, Deddy; Yermadona, Helga; Wailussy, Idris (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2019)
Lubuk Alai - Koto Lamo road is an agricultural and tourism lane located in Lima Puluh Kota, West Sumatra, so that this road holds an important role in the economic sector. The purpose of this study is to compare the planning of thick pavement liners by using Bina Marga Component Analysis 1987 method and AASHTO 1993 method on the Lubuk Alai - Koto Lamo road STA 0 + 000 to STA 3 + 800 Lima Puluh Kota Districts. The method used to analyze the data is Bina Marga Component Analysis 1987 method and AASHTO 1993. The results obtained that in 10 year planning for Component Analysis the thickness of 5 cm MS 340 Laston surface course, the base course of Class A thick Aggregate 15 cm and the subbase course of Sirtu Class B thickness is 10 cm. With using AASHTO 1993 analysis the thickness of 11 cm MS 340 Laston surface course, the base course of Class A thick Aggregate 8 cm and the subbase course of Sirtu Class B thickness is 18 cm.